A Condensed Introduction to the Doubly Fed Induction Generator Wind Energy Conversion Systems. (22nd June 2017) - Mwaniki, Julius; Lin, Hui; Dai, Zhiyong
Abstract : The increase in wind power penetration, at 456 GW as of June 2016, has resulted in more stringent grid codes which specify that the wind energy conversion systems (WECS) must remain connected to the system during and after a grid fault and, furthermore, must offer grid support by providing reactive currents. The doubly fed induction generator (DFIG) WECS is a well-proven technology, having been in use in wind power generation for many years and having a large world market share due to its many merits. Newer technologies such as the direct drive gearless permanent magnet synchronous generator have come up to challenge its market share, but the large number of installed machines ensures that it remains of interest in the wind industry. This paper presents a concise introduction of the DFIG WECS covering its construction, operation, merits, demerits, modelling, control types, levels and strategies, faults and their proposed solutions, and, finally, simulation. Qualities for the optimal control strategy are then proposed. The paper is intended to cover major issues related to the DFIG WECS that are a must for an overview of the system and hence serve as an introduction especially for new entrants into this area of study.